Penyalahgunaan Wewenang Aparat Kepolisian Dalam Perspektif Good Governance: Studi Kasus Ferdy Sambo - Ida Muthia Zahra; Siti Nur Azizah; Jihan Fasabilla; Rindi Lutfiana; Wijdan Arif Rizaldi (ANTASENA: Governance and Innovation Journal, 2026)
The abuse of authority by police officers is a form of power deviation that can hinder the realization of good governance and reduce public trust in law enforcement institutions. The Ferdy Sambo case represents a clear example of abuse of authority within the police institution, involving not only criminal violations but also reflecting weaknesses in institutional governance and internal supervision. This study aims to analyze the forms of abuse of authority by police officers from a good governance perspective through the Ferdy Sambo case study. The research employs a qualitative method using a literature study approach by collecting data from academic journals, books, legal regulations, and other relevant sources, which are then analyzed using content analysis techniques. The findings reveal that the abuse of authority occurred in the forms of exceeding authority, misuse of authority, and arbitrary actions, influenced by weak internal supervision, a hierarchical bureaucratic culture, strong personal loyalty to superiors, and low accountability and transparency within the police organization. The impacts of such abuse include declining public trust in the Indonesian National Police, damage to the institution’s reputation, and disruption of fair law enforcement processes. This study concludes that strengthening good governance principles through improved supervision, integrity, professionalism, and accountability is essential to prevent the recurrence of abuse of authority within police institutions and to support the realization of a more transparent, accountable, and trustworthy law enforcement system in Indonesia.